The effect of different tethered forces on assisted freestyle swimming performance - Moriyama, S.; Kurono, T.; Watanabe, Y.; Wakayoshi, K. (The Journal of Physical Fitness and Sports Medicine, 2018)
[Purpose] Assisted swimming is one of the popular training regimes for improving swimming performance; it increases swimming velocity to faster than required the competitive race. However, the setting of tethered force is based on the experience and sense of coaches and swimmers. Therefore, the present study aimed to clarify the effect of different tethered forces in assisted swimming on swimming performance. [Methods] Twelve collegiate highly trained competitive swimmers (8 men and 4 women) performed one trial of 25 m front crawl swimming with maximal effort without using a towing machine, and five trials of swimming that were set at five different tethered forces (36, 71, 107, 142 and 178 N) using a towing machine. Swimming velocity and force were measured as indices of swimming performance. [Results] The mean value of maximal swimming force was 137.5±26.1 N. The swimming velocity during five different tethered forces were 36N (1.92±0.10 m.s-1), 71N (2.10±0.09 m.s-1), 107N (2.26±0.06 m.s-1), 142N (2.30±0.04 m.s-1) and 178N (2.31±0.03 m.s-1); a significant difference was observed between the 142N and 178N. [Conclusion] Increase in the swimming velocity with different tethered forces using a towing machine would reach nearly maximum at 142 N. The maximal swimming velocity using a towing machine would not be related to the maximal swimming force in individuals.